Denmark : Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
The paper discusses findings of the Financial System Stability Assessment for Denmark. The Danish authorities have taken important steps to improve financial system resilience. Financial regulation and supervision have been strengthened. A new bank resolution framework that includes bail-in of creditors has been adopted and deployed to resolve small- and medium-sized banks. An institutional framework for macroprudential policy has also been adopted. Recent legislation requires maturity extension of covered bonds in stress situations, with the aim of reducing refinancing risk in the mortgage finance system. Although stress tests suggest that financial stability risks are contained, the financial system's large size and interconnectedness call for additional measures to further strengthen resilience.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet